Chivalry - Gaiman, Neil (Dark Horse Books, 2022)
"An elderly British widow buys what turns out to be the Holy Grail from a second-hand shop setting her off on an epic visit from an ancient knight who lures her with ancient relics in hope for winning the cup"--